The priestly gift of Mishnah : a study of tractate Terumot - Avery-Peck, Alan J. (Brown Judaic studies, 2020)
"This study systematically analyzes Tractate Terumot (heave-offerings) in the Mishnah and its corresponding document, the Tosefta. It provides a new translation of and commentary on Terumot and considers the shape and message of the tractate as a whole."--Provided by publisher